2004
DOI: 10.1074/jbc.m314118200
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2 Inhibits Bay 11-7085-induced Sustained Extracellular Signal-regulated Kinase Phosphorylation and Apoptosis in Human Articular Chondrocytes and Synovial Fibroblasts

Abstract: We have previously shown that nuclear factor-B inhibition by adenovirus expressing mutated IB-␣ or by proteasome inhibitor increases human articular chondrocytes sensibility to apoptosis. Moreover, the nuclear factor-B inhibitor BAY11-7085, a potent anti-inflammatory drug in rat adjuvant arthritis, is itself a proapoptotic agent for chondrocytes. In this work, we show that BAY 11-7085 but not the proteasome inhibitor MG-132 induced a rapid and sustained phosphorylation of extracellular signal-regulated kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 36 publications
2
53
0
2
Order By: Relevance
“…Previous reports have described additional effects of Bay 11 compounds on the ERK, JNK, and p38 MAPK (43). Ligand occupancy of TLRs by their cognate PAMPs activates several wellcharacterized signaling pathways within monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports have described additional effects of Bay 11 compounds on the ERK, JNK, and p38 MAPK (43). Ligand occupancy of TLRs by their cognate PAMPs activates several wellcharacterized signaling pathways within monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…Further analysis in synovial fibroblasts showed that only molecules that suppressed BAY 11-7085-induced phosphorylation of ERK (i.e. 15-d-PGJ 2 , PGD 2 , and to a lesser extent, MEK inhibitor U0126, but not PGE 2 and PGF 2· ) were able to protect cells from apoptosis (45). In diosgenin-induced apoptosis in human RA FLS, we showed that p38 inhibitor (SB203580), JNK inhibitor (SP600125) and MEK inhibitor (U0126) decreased diosgenin-induced COX-2 mRNA and protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that apoptosis induced by diosgenin (40 μM) in human RA FLS inhibited NF-κB binding and activated p38 MAPK without increasing 15-d-PGJ 2 synthesis. However, it has been recently shown that the NF-κB inhibitor BAY11-7085, a potent anti-inflammatory drug in rat adjuvant arthritis, induced apoptosis of chondrocytes and human synovial fibroblasts with a rapid and sustained phosphorylation of ERK (45). Further analysis in synovial fibroblasts showed that only molecules that suppressed BAY 11-7085-induced phosphorylation of ERK (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that PPAR-␥ agonist 15d-PGJ2 protects human synovial fibroblasts from BAY 11-7085-induced apo-ptosis (16). Analysis of PPAR-␥ expression, as described here, showed that synovial fibroblasts constitutively express PPAR-␥1, which is dephosphorylated and degraded during BAY 11-7085-induced apoptosis.…”
mentioning
confidence: 51%